An innovative oncoplastic technique for immediate small to medium volume breast reconstruction in lower inner quadrant cancer: The Zhuo-technique. (August 2021) - Shi, Wenjie; Torres-de la Roche, Luz Angela; Ritter, Henning; Dong, Jie; Zeng, Jia-Jia; Jiang, Yi-Cheng; Zhuo, Rui; De Wilde, Rudy Leon
Abstract: Background: Insufficient glandular tissue in the lower quadrant of the breast is the main source of difficulty in repairing defects after oncoplastic surgery. Especially in small to medium sized breasts, this issue is more common. Here, we describe a novel oncoplastic approach that could help to solve this problem. Materials and methods: Retrospective analysis of breast cancer patients with tumors in the lower inner quadrants, who underwent Zhuo's technique between January 2017 and August 2019. Aesthetic outcomes were evaluated in terms of the Paris Breast Center's 5-point scale. The work was reported according to the STROCSS criteria. Results: Nine patients (mean age 54 years) with small to medium volume breast received Zhuo's oncoplastic technique after tumor excision. The mean size tumor was 18.0 mm. The median follow-up time was 27.0 months. Sentinel lymph node biopsy results for all patients were negative. None of the patients had local recurrences or metastases and postoperative complications were not observed. Seven patients (77.8%) achieved aesthetic scores of 5 and two patients (22.2%) achieved 4 points. Conclusions: Zhuo's oncoplastic technique could provide a favorable and flexible surgical approach for small to medium volume breast with tumors of the lower inner quadrant with a low risk of recurrence and good aesthetic results. Protocol register: Chinese clinical trial register No. ChiCTR2100043484. Highlights: Defects after oncoplastic surgery is complicated by a lack of glandular tissue specially in case of small volume breasts. The Zhuo-technique generates a flexible pedicle flap from the upper abdomen to fill the defect area. The Zhuo-technique allows sufficient tissue transposition improving the postsurgical aesthetic appearance.